Characterization of a patatin-like phospholipase involved in lipid droplet biology in Trypanosoma brucei - (:unkn) unknown (My University, 2024)
African trypanosomes are flagellated protozoan parasites responsible for deadly diseases in humans (Human African trypanosomiasis or sleeping sickness) and animals (animal African trypanosomiasis or Nagana). Trypanosoma brucei is the study model for these pathogens. This parasite alternates between a mammal host and a bloodsucking insect that allows vectorial transmission, the tsetse fly, found in Sub-Saharan Africa. During this lifecycle, the pathogen must cross several tissues (skin, bloodstream and lymph and adipose tissue in the mammal; midgut and salivary glands in the insect), and shows great capacities of adaptation in these different environments. To complete this cycle and adapt to its hosts, T. brucei is able to quickly modify its morphology and metabolism. In this context, the mobilization and utilization of lipids is particularly essential to the parasite’s survival. These molecules are involved in various cellular processes, including the maintenance and renewal of cellular membranes (made of phospholipids), energy metabolism, cellular signaling pathways and gene expression regulation. This mobilization is made possible by a highly dynamic compartment called lipid droplets. This atypical organelle, surrounded by a monolayer of phospholipids, forms a metabolic platform and represents a growing interest in human health due to its potential roles in metabolic and neurodegenerative diseases, as well as cancers. In protozoan parasites, the very recent interest in lipid droplets shows roles in the survival and virulence in the mammal host.The objective of this thesis was to identify and characterize new proteins associated with the lipid droplets of T. brucei to understand the organelle’s function in the parasite. We discovered a new phospholipase of the patatin-like family, which we called TbPat. We showed through different imaging techniques that TbPat localizes to the surface of the lipid droplets of the parasites. The expression of this
Keywords: African Research